Phenolic compounds and antioxidant activities in dehusked and polished pigmented rice varieties - Jayaraman, Rajarajeswari; Yadavalli, Chandrasekhar; Singh, Vasudeva; Khanum, Farhath (ORYZA-An International Journal of Rice, 2019)
Present study was conducted to characterise eight red rice varieties in their de-husked and polished form for their phytochemical contents and anti-oxidant activities. Ferulic acid, gallic acid, quercetin, vanillic acid and rutin were identified in their free phenolic extracts. Dehusked rice free phenolics prevented free radical formation, metal chelation ferric to ferrous reduction and also influenced the reducing power. In polished rice, a moderate increase in antioxidant properties was noticed. The methanol extract showed higher phenolic content and antioxidant activities compared to extracts made in other solvents. Dehusked form of Kamdhari, Black basumati, Sirsi and Jyothi varieties exhibited higher amount of phytochemical components and antioxidant activities among the varieties. In dehusked form, total carotenoid content was more in Aravadan pillai and GK-4 varieties, whereas ascorbic acid content was high in Karisale, Kamdhari, Black basmati, Sirsi and Kasubai varieties. Thus, the dehusked and polished rice of these varieties with sufficient phenolic contents appear to be more useful as compared to normal rice with respect to their antioxidant properties.